PILOT APPLICATION ANALYSIS AND DESCRIPTION FOR AN AUTHOR OFFERED NEW APPLICATION - Petkevičs, Dmitrijs; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The givens paper’s “Pilot application analysis and description for an author offered new application” goal is to analyze the apps available for pilots. During research author made multiple groups of applications that pilots use to make their work easier, and described them. Also author offered a new application that will help pilots in daily reports. Conclusion was made using knowledge gathered from analyzes.